ANALISIS DISTRIBUSI CURAH HUJAN MENGGUNAKAN METODE LOG PEARSON III - Raymond Pasaribu; M Kaysan Nawfal; Oersted Melkgior Siburian; Anasya Arsita Laksmi (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
Rainfall frequency analysis is essential for determining design rainfall and flood discharge in hydraulic structure planning. In this study, annual maximum rainfall data were evaluated using statistical parameters—including the coefficient of variation, skewness coefficient, and kurtosis coefficient—to determine the most suitable probability distribution. The Log-Pearson Type III distribution was selected as it best represented the historical data patterns. Design rainfall values for various return periods were subsequently computed to construct Intensity-Duration-Frequency (IDF) curves. Watershed delineation was performed to identify the physical characteristics of the river basin, allowing the transformation of design rainfall into peak flood discharges. The results demonstrate that longer return periods consistently yield higher rainfall intensities and peak discharges. Ultimately, this study provides critical hydrological parameters required for effective drainage design and regional flood control.